Prawa Przedsiębiorców na gruncie ustawy o SENT - Kanarek-Równicka, Anna (PRAWO i WIĘŹ, 2025)
This paper addresses issues that are important in terms of the liability of entrepreneurs for violating the principles of monitoring the transport of sensitive goods and the trade of heating fuels, as set out in the SENT Act. The high and strictly defined fines for breaching the reporting obligations imposed by the SENT Act, and the inability to moderate them, constitute an administrative sanction for entrepreneurs’ lack of self-control in such economic activities. While the legislator provided for the possibility of refraining from imposing a fine, the construction of the relevant provision was based on the discretion of the body conducting the proceedings. However, the previous practice of waiving fines shows that this institution was used extremely rarely, and the body conducting the proceedings was guided exclusively by the literal wording of the SENT Act provision. Recent case law from the Supreme Administrative Court emphasises the need to assess the advisability of imposing an administrative penalty, taking into account the premise of the necessity of imposing a fine. The provisions of the SENT Act and the content of the vague and imprecise terms used therein cannot be interpreted arbitrarily, as this could lead to a violation of the principle of proportionality when imposing a penalty for an infringement.